Remembering The Athenian Defeat At Chaeronea - Rung, Eduard (2018)
The paper considers the Athenians’ reaction to the battle of Chaeronea in 338 B.C. as reflected in the oratory. The authors focus on the rhetoric of defeat and contrast it with the rhetoric of victory, which occurs in the same orators who remembered and commemorated the events of the Athenian glorious past in their orations. This paper also includes all relevant exempla from these orations, which deal with heroism and patriotism, on the one hand, and treachery, on the other hand. It is argued that an important rhetoric method was to make contrast between the present and the past wars as well as the patriotism and the treason in the speeches specially dealing with the defeats. It is concluded that the rhetorical and emotional representation of the events is pre-vailing over the historical one since the main aim of the orators is to manipulate with the historical memory of the people for their objectives.